Uniaxial stress dependence of ferroelectric properties of xPMN-(1-x)PZT ceramic systems - Yimnirun R. (2014)
Effects of uniaxial compressive pre-stress on the ferroelectric properties of ceramics in the PMN-PZT system are investigated. The ceramics with a formula xPb(Mg1/3Nb2/3)O3-(1-x)Pb(Zr 0.52Ti0.48)O3 or xPMN-(1-x)PZT when x=0.0, 0.1, 0.3, 0.5, 0.7, 0.9, and 1.0 are prepared by a conventional mixed-oxide method. The ferroelectric properties under the uniaxial compressive pre-stress of the PMN-PZT ceramics are observed at the stress levels up to 13 MPa using a compressometer in conjunction with a modified Sawyer-Tower circuit. It is found that with increasing compressive pre-stress levels the area of the ferroelectric hysteresis (P-E) loops, the saturation polarization (Psat), the remanent polarization (Pr), and the coercive field (Ec) decrease. These results are interpreted through the non-180° ferroelastic domain-switching processes. Finally, the calculated differential permittivity for all the xPMN-(1-x)PZT ceramics, except for 0.5∈PMN-0.5∈PZT, decreases with increasing applied stress. © Springer-Verlag 2005.